Review of Scheduling Algorithms in Cloud Computing Environment (International Journal of Engineering and Computer Science, 2017)
Cloud Computing refers to the use of computing, platform, software, as a service. It’s a form of utility computing where the customer need not own the necessary infrastructure and pay for only what they use. Computing resources are delivered as virtual machines. In such a scenario, task scheduling algorithms play an important role where the aim is to schedule the tasks effectively so as to reduce the turnaround time and improve resource utilization. This paper reviews various scheduling algorithms in cloud environment.